Social networks and organizational helping behavior: Experimental evidence from the helping game - Hande Erkut; Ernesto Reuben (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
This paper studies the causal impact of social ties and network structure on helping behavior in organizations. We introduce and experimentally study a game called the 'helping game,' where individuals unilaterally decide whether to incur a cost to help other team members when helping is a rivalrous good. We find that social ties have a strong positive effect on helping behavior. Individuals are more likely to help those with whom they are connected, but the likelihood of helping decreases as the social distance between individuals increases. Additionally, individuals who are randomly assigned to be more central in the network are more likely to help others.
Keywords: D23; D91; 330; helping; social ties; social networks; communication; organizations